EDUKASI POLA MAKAN SEHAT DAN AKTIVITAS FISIK MENGGUNAKAN BOARD GAME DI PANTI ASUHAN DHARMA LAKSANA KOTA MATARAM - Sari, Dian Puspita; Abdiman, I Made Tobias; Maringka, Kezia Michella Yusak; Manafe, Winda; Patandianan, Firdaus Kamma (Jurnal Abdi Insani, 2024)
The prevalence of obesity among children and adolescents is rising globally, leading to short- and long-term health issues such as type 2 diabetes (Type 2 DM). While obesity has multiple causes, modifiable lifestyle factors like diet and physical activity can reduce the risk Indonesian children are exposed to high-sugar, low-nutrient foods and engage in limited physical activity, increasing their risk for obesity and Type 2 DM. Although children depend on adults for food, they must learn to make healthy choices early on. This community service activity aimed to improve knowledge and promote healthy eating and physical activity among foster children at the Dharma Laksana Orphanage in Mataram City. A brief survey found that 33-60% of the children chose high-sugar foods over healthier options. Education was delivered through presentations and a custom-developed board game, "Pilah Pilih" (Select and Choose), which included a storybook and guide. Forty children and two caregivers participated. Post-activity evaluations showed 60% of children scored above 70 in knowledge assessments, with a highest score of 85. Feedback on the game indicated positive engagement and enthusiasm for replay. The "Pilah Pilih" board game shows potential as an effective educational tool to encourage behavioral change through repeated play.